A Direct Instruction and Precision Teaching Intervention to Improve the Sentence Construction of Middle School Students With Writing Difficulties. (August 2017) - Datchuk, Shawn M.
Being able to construct simple sentences is necessary for effective written expression. The present study investigated effects of a sentence construction intervention on small groups of middle school students with disabilities and writing difficulties. The intervention entailed sentence instruction and frequency building to a performance criterion, a type of timed practice emphasizing fluency. A single case design, multiple-baseline across small groups, was used. Three middle school teachers delivered intervention to three small groups of students (a total of 15 students). As a result of intervention, the average number of correct minus incorrect word sequences per small group gradually increased. Results are discussed in the context of the sentence construction literature and within a framework of direct instruction and precision teaching.